RANCANG BANGUN ALAT HITUNG ELEKTRONIK SEDERHANA UNTUK TUNA NETRA MENGGUNAKAN KONVERSI TEKS KE SUARA DENGAN ISD 2590 - Mochammad Iqbal; Muhamad Yusuf (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2016)
People with special needs need to get equality in the use of technology. One is technological tools such as a calculator to count. Calculator is a tool for human arithmetic, but in reality not all the calculators can be used in humans. Lack of facilities for blind persons is difficult for them in the process of calculations using the calculator. Need to develop a calculator that can petrify blind persons to perform the calculation process. By using the voice of the speaker via a series of ISD 2590, ATmega16 as the main control, 4x4 keypad as number operations, 2x16 LCD as a viewer of the results of operations of numbers, and Braille, it creates tools for the blind count. From the results of testing the system as a whole, these tools can only perform number operations as addition, subtraction, multiplication, and division. This tool can also operate for the fractions and round.